2020
DOI: 10.3390/ijerph17249594
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Sense of Coherence of Dental Hygiene Students in Their Graduation Year and Their View of the Profession and Attitude to Work: A Cross-Sectional Survey in Japan

Abstract: Objective: The need to make sense of coherence in placement support for student dental hygienists has been shown. On this basis, this study investigated the relationship between the sense of coherence of student dental hygienists and their view of the profession and attitude to work in order to clarify how they perceive their prospects for employment. Methods: The subjects were graduation-year students at all of the dental hygienist training institutions in Japan, and anonymous, self-administered questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…There are also multiple reports on the potential effectiveness of using SOC in educational settings. The results show that students with higher SOC scores are more motivated to learn [24] and have a better view of their work [25]. The results also show that professional involvement can improve SOC scores [26].…”
Section: Training Support Built Upon Soc Trendsmentioning
confidence: 79%
“…There are also multiple reports on the potential effectiveness of using SOC in educational settings. The results show that students with higher SOC scores are more motivated to learn [24] and have a better view of their work [25]. The results also show that professional involvement can improve SOC scores [26].…”
Section: Training Support Built Upon Soc Trendsmentioning
confidence: 79%
“… 25 Moreover, improving dental hygiene students’ sense of coherence, which is related to their view of the profession, was associated with an increase in the number of years they wanted to work as DHs and in their job satisfaction. 26 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have also found that middle-aged women performing higher academic results develop better self-care levels, and these students also obtained more powerful scores in their SOC, as the findings of the major systematic review on the SOC in nurses suggest [ 74 ]. More investigations report that those students showing strong SOC values are more resistant to stress, keep healthier behaviours, show higher professional engagement, and, furthermore, theoretical assumptions determine that they do better academically [ 75 , 76 , 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%